Horas complementarias - Yumbo Andy, Katy Maritza (2016)
This research project aimed to make a diagnosis of compliance with the additional hours by teachers of the Education Unit Victoria "Vásconez Cuvi" - "Simon Bolivar"; the development of additional hours is important in the education system; these hours are performed by teachers with operational shortcomings. This problem does not allow the full implementation of teachers in the teaching-learning process, undoubtedly affecting students who fail to welcome the skills and knowledge in different areas of study. To develop the research process was resorted to methods such as analytic, synthetic, historical - logical, comparative scientific; in the same way techniques and instruments for gathering information such as survey and questionnaire they were applied respectively. The results of the investigation show falencia professional teachers to meet current legislation create a serious impact on the achievement of goals and quality standards of education. These results allow conclusions summarize in turn constituted essential elements to establish general recommendations for both the institution and the School of Basic Education generative spaces that generate research that contribute with proposals to solve the problem.